Spontaneous Twin Pregnancy in Uterus Bicornis Unicollis - Arzu Doruk; Ilay Gozukara; Güneş Burkaş; Esin Bilik; Talat Umut Kutlu Dilek (Hindawi Limited, 2013)
Abnormal fusion of the Müllerian ducts or failure of resorption of the septum causes varying degrees of congenital uterine malformation. They are often associated with reproductive problems such as miscarriage, premature labour, premature rupture of the membranes, or malpresentation. Twin gestation in a case of bicornuate uterus is extremely rare. A 37-year-old multiparous woman conceived a twin dichorionic diamniotic pregnancy spontaneously. Three-dimensional ultrasound revealed bicornuate uterus with one embryo in each cavity. Perinatal course was uneventful. At 35 weeks of pregnancy, spontaneous labour started and twin babies were delivered by bilateral low transvers caesarean section. Because of the rare occurrence of twin gestation in bicornuate uterus, there is no uniform guideline to manage these cases appropriately. Delivery by planned caesarean section could avoid the possible obstetric complications by dystocia.